Community-Informed Mobile COVID-19 Testing Model to Addressing Health Inequities. (January 2022) - Jiménez, Jonathan; Parra, Yury J.; Murphy, Katherine; Chen, Alexandra Nixxi; Cook, Andrew; Watkins, Jacob; Baker, Melissa D.; Sung, Semi; Kaur, Guneet; Kress, Marielle; Kurien, Sarah Joseph; Keeley, Chris; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Context: The New York City (NYC) Test & Trace Corps (Test & Trace), under New York City Health + Hospitals (NYC H+H), set out to provide universal access to COVID-19 testing. Test & Trace partnered with numerous organizations to direct mobile COVID-19 testing from concept through implementation to reduce COVID-19-related health inequities. Program: Test & Trace employs a community-informed mobile COVID-19 testing model to deliver testing to the hardest-hit, underserved communities. Community partners, uniquely knowledgeable of the residents they serve, are engaged as decision makers and operational partners in mobile COVID-19 testing delivery. Implementation: Through several mobile testing methods, community partners choose testing locations and tailor outreach to their community. Test & Trace assumes logistical responsibility for mobile testing but defers critical programmatic decisions and community engagement to partners. Integral to the success of this program is responsive, bidirectional communication. Evaluation: During the reporting period of December 1, 2020, to April 30, 2021, Test & Trace's community-informed mobile COVID-19 testing model provided testing to 150351 unique patients and processed 274083 tests in total. The available outcomes data and qualitative feedback provided by community partners illustrate that this intervention, combined with robust governmental investment, successfully ensured that NYC-identified, low-resource neighborhoods had greater access to COVID-19 testing. Discussion: Making community partners decision makers reduced inequities in access to testing for communities of color. In addition, the model has served as the framework for Test & Trace's community-informed mobile COVID-19 vaccination program, operated in concert with NYC's Vaccine Command Center, and is a foundation for addressing health inequities at scale, including during public health crises.